2005
DOI: 10.1539/joh.47.85
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practices Related to Occupational Health Problems among Salt Workers Working in the Desert of Rajasthan, India

Abstract: Knowledge, Attitude and Practices

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 6 publications
4
12
0
Order By: Relevance
“…It may also be as a result of the weak enforcement of labour laws in the country, ignorance of the law among workers, as well as the high level of unemployment in the country that leaves the worker desperate for employment and at the mercy of his employer Knowledge of road construction hazards was found to be good (94.9%) among the construction workers in this study. This finding is similar to what was obtained in a study carried out in of Rajasthan, India [9] among brine workers where knowledge of occupational hazards was found to be good (98.7%). It is important to point out that differences in criteria used to assess knowledge might have also contributed to this finding.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It may also be as a result of the weak enforcement of labour laws in the country, ignorance of the law among workers, as well as the high level of unemployment in the country that leaves the worker desperate for employment and at the mercy of his employer Knowledge of road construction hazards was found to be good (94.9%) among the construction workers in this study. This finding is similar to what was obtained in a study carried out in of Rajasthan, India [9] among brine workers where knowledge of occupational hazards was found to be good (98.7%). It is important to point out that differences in criteria used to assess knowledge might have also contributed to this finding.…”
Section: Discussionsupporting
confidence: 91%
“…The study concluded that improvements in protective devices are needed to increase their acceptability. [9] Another cross-sectional study was carried out on workers in MahshahrRazy Petrochemical Complex in Iran. The aim was to determine the level of knowledge, attitude and behavior of Workers towards occupational health and safety.…”
Section: Introductionmentioning
confidence: 99%
“…Safe practice did not depend on knowledge and attitude but was positively associated with being informed of safety precautions and being supplied with chemical information by supervisors. Another study(3) also reported a huge gap between the knowledge and practice of salt workers with protective devices. KAP related to occupational health problems among garment workers in Tamil Nadu, India, revealed that the workers employed in the three sections had high levels of knowledge of health problems, but the knowledge of PPE differed by section.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies related to KAP of different category of workers have been reported in the literature, but this is the first systematic study to reveal KAP and the underlying factors that influence the health problems of garment workers. A study of printing workers in Hong Kong by Yu and colleagues indicated that safe practice did not depend on knowledge and attitude but was positively associated with being informed of safety precautions and being supplied with chemical information by supervisors 2) . A similar study conducted among 205 salt workers also revealed that the workers had good knowledge about the health problems and the protective measures, but a huge gap could be observed between the knowledge and usage of PPE, mainly due to the non-availability of safety devices, high cost and safety devices not provided by the salt manufacturers 3) .…”
Section: Discussionmentioning
confidence: 99%